Living under the crescent moon : - editor, Mateo Kries, Alexander von Vegesack ; translations: Jeremy Gaines, Julia Taylor Thorson, William Stoddart]. (Vitra Design Museum, 2003)
Exhibition catalog. Exhibition in Weil am Rhein, Vitra Design Museum, until January 18, 2004.